Migration-related emotional distress among Vietnamese psychiatric patients in Germany: An interdisciplinary, mixed methods study. (December 2021) - Nguyen, Main Huong; Lanca, Jörg-Christian; Hahn, Eric; von Poser, Anita; Heyken, Edda; Wingenfeld, Katja; Burian, Ronald; Diefenbacher, Albert; Ta, Thi Minh Tam
Culture and socialization influence how individuals perceive and express emotional distress. Research therefore, must consider the context to capture individual experiences. However, the majority of studies on factors associated with emotional distress among migrants use quantitative approaches, limiting an in-depth understanding. This study investigates emic themes of emotional distress among Vietnamese migrants by integrating anthropological and psychiatric approaches. The mixed methods study first quantified differences in reported themes of distress between Vietnamese ( n  = 104) and German ( n  = 104) patients, who utilized two psychiatric outpatient clinics in Berlin, Germany. Based on these differences, ethnographic interviews were conducted with 20 Vietnamese patients. In the quantitative part, differences in frequency of reported distress between Vietnamese and German patients indicate cultural and migration-related issues among Vietnamese migrants, such as the upbringing of children in a transcultural context. In the qualitative part, interviews with Vietnamese patients elicited contextualizing information and additional themes of distress. Besides commonly expressed socioeconomic themes, such as work and finances, we identified affectively charged themes concerning roles toward partnership and children. A central emic theme is expressed as "moments of speechlessness, " which go beyond a lack of language proficiency and challenge patients in different spheres of life. Migration entails complex affective dynamics, determined by a specific migratory and post-migratory context. Within this context, norms and values determine which themes of distress patients articulate openly. Therefore, an interdisciplinary, mixed-methods approach can yield a contextualized understanding of emotional distress and the complex nature of migration.